Propuesta de la Documentación del Sistema de Gestión de la Calidad con Base a la NTC ISO 9001: 2015 en la Empresa Agua Diamante de Santa Marta, Magdalena (2023)
This paper presents a proposal for the documentation of the Quality Management System based on the NTC ISO 9001 version 2015 in the company Agua Diamante located in the city of Santa Marta, which is dedicated to bottling, distribution, packaging and marketing of drinking water. First, a survey was conducted to collect the necessary information and analyze the current situation according to the requirements of the standard. Next, a diagnosis is applied and it is evaluated whether or not it complies with the compliance parameters of the NTC ISO 9001 version 2015. The purpose of the documentation is to analyze, evaluate and improve the current situation and interactions of the company, so that all relevant requirements are met to achieve continuous improvement, and achieve the objectives of the organization and meet every need and expectation of the customer.